Determinant of Neonatal Visit Coverage Rate in Serdang Bedagai Regency North Sumatra Indonesia - Novita Br Ginting Munthe; Rizanda Machmud; Rima Semiarty; Joserizal Serudji; Adang Bachtiar; Finny Fitry Yani; Denas Symond; Nelwati Nelwati (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Neonatal mortality is a leading cause of infant deaths, particularly in developing countries. In Serdang Bedagai Regency, the coverage of neonatal visits remains low, contributing to the high neonatal mortality rate and causing economic losses. This study aims to identify factors related to the neonatal visit coverage rate in Serdang Bedagai Regency, North Sumatra, Indonesia. This study used a cross-sectional design with multivariate analysis. Data were collected from 200 mothers with babies aged 0-28 days in five health centers in Serdang Bedagai Regency. The variables analyzed include age, education, economic status, knowledge, maternal attitudes, culture, family support, midwife attitudes, access to health facilities, and service quality. The data were analyzed using logistic regression. The results showed that the variables consistently and significantly affecting the increase in neonatal visit coverage were maternal education, knowledge about neonatal visits, local culture, husband/family support, and the quality of visit services. Factors that significantly contributed to increasing coverage of neonatal visits were maternal education (p-value = 0.004, OR = 14.285), maternal knowledge (p-value = 0.000, OR= 75.920), local culture (p-value = 0.000, OR = 57.105), husband/family support (p-value = 0.000, OR = 77.763), and service quality (p-value = 0.000, OR = 47.474). These factors have a major influence in supporting the success of the neonatal visit program, with maternal knowledge and family support being the most dominant factors.. Efforts to increase coverage should involve educating mothers, involving families, and enhancing services while considering local wisdom.